Answer:
U'(3, -6), V'(8, -1), W'(3, -1)
Step-by-step explanation:
According to the 180°-rotation rule, you take the OPPOSITE of both the y-coordinate and x-coordinate:
Extended Rotation Rules
270°-clockwise rotation [90°-counterclockwise rotation] >> (x, y) → (-y, x)
270°-counterclockwise rotation [90°-clockwise rotation] >> (x, y) → (y, -x)
180°-rotation >> (x, y) → (-x, -y)
I am joyous to assist you anytime.
0
-8
Answer:
49
Step-by-step explanation:
The given function is .
We expand to get:
We complete the square to obtain the vertex form as follows:
This function is now of the form:
, where (h,k)=(-4,49) is the vertex.
The y-value of the vertex is therefore 49
circle, which could represent the equation of the new
circle?
O (h + x)2 + (k + y)2 = 22
0 (x – n)2 + (y – k)2 = p2
O (k + x)2 + (h + y)2 = 22
0 (x – k)2 + (y – 5)2 = 12
The equation of the new circle will be,
⇒ (x - h)² + (y - k)² = r².
The circle is a closed two dimensional figure , in which the set of all points is equidistance from the center.
Now, If the center of the circle were moved from the origin to the point (h, k) and point P at (x, y) remains on the edge of the circle.
Then, Equation of the new circle,
(x - h)² + (y - k)² = r²
Where center = (h, k)
radius = r
Hence, the equation of the new circle will be,
⇒ (x - h)² + (y - k)² = r².
Learn more about the circle visit:
#SPJ7
Answer:(x-h)^2+(y-k)^2=r^2
Step-by-step explanation:
I just answered it and it’s correct
The simplifiedexpression is 47.
An expression contains one or more terms with addition, subtraction, multiplication, and division.
We always combine the liketerms in an expression when we simplify.
We also keep all the like terms on one side of the expression if we are dealing with two sides of an expression.
Example:
1 + 3x + 4y = 7 is an expression.
3 + 4 is an expression.
2 x 4 + 6 x 7 – 9 is an expression.
33 + 77 – 88 is an expression.
We have,
To simplify this expression, we need to follow the order of operations, which is:
PEMDAS:
Parentheses, Exponents, Multiplication, Division (from left to right), and Addition and Subtraction (from left to right).
There are no parentheses or exponents in the expression, so we move on to multiplication and division.
We have 4 times 5, which is 20.
55 - 20 + 12
Now we can perform addition and subtraction.
We have 55 minus 20, which is 35.
35 + 12 = 47
Therefore,
The simplifiedexpression is 47.
Learn more about expressions here:
#SPJ3
Answer:
The answer is 47.
Step-by-step explanation:
From PEMDAS we know that for this problem, we do the Multiplication first, then the Addition and Subtraction.
55-4*5+12 =
55-20+12 =
35 + 12 = 47
15.7 ÷ 3.2 =